Answer:
1) 2(t - 7)(t + 1)
2) $32,000
Step-by-step explanation:
v(t) = 2t² - 12t - 14
v(t) = 2(t² - 6t - 7) = 2(t - 7)(t + 1)
x = -b/2a = 6/2 = 3
y = 2(3)² - 12(3) - 14 = -32
(3, -32) means at 3 months, -32 thousand dollars
The correct answer is B. -12
I guess you are asking to find the sum of the first 8 terms. If so, then:
Sum = a₁(1-rⁿ)/(1-r), where a₁ is the 1st term, r=common ratio and n=number of terms:
the 1st term a₁ =3
common ratio r = - 2 (since -6/3 = - 2, and 12/-6 = - 2, etc.)
Sum = 3[(1- (-2)⁸]/(1-2) = 3(1- 256)/(1/2)
Sum = -1530
Answer:
a = 5
Remainder when p(x) is divided by x+2 = 62
Step-by-step explanation:
Given:
P(x) = x⁴-2x³+3x²-ax+3a-7
When x+1 divides the polynomial p(x) the ramainder is 19.
Applying remainder theorem,
x = -1
p(-1) = 19
Substitute the x = -1 into the polynomial expression
p(-1) = (-1)⁴-2(-1)³+3(-1)²-a(-1)+3a-7 = 19
1+2+3+a+3a-7 = 19
6-7+4a = 19
4a-1 = 19
4a = 19+1
4a = 20
a = 20/4
a = 5.
Hence, a = 5
p(x) = x⁴-2x³+3x²-5x+8
If p(x) is divided by x+2,
Then the remainder is p(-2)
p(-2) = (-2)⁴-2(-2)³+3(-2)²-5(-2)+8
p(-2) = 16+16+12+10+8
p(-2) = 62
Hence the remaider when p(x) is divided by x+2 is 62
First box, third box, fifth and also sixth =D